Burnout y compromiso organizacional en profesionales de la salud - Vargas Tejada, Xiomara Aracelly (2021)
Burnout is a syndrome that mainly affects healthcare professionals and their organizational commitment, which in turn may have negative consequences on the service they provide. The aim of this study is to describe the relationship between burnout and organizational commitment among healthcare professionals through a systematic review of scientific articles. To this end, a systematic review of the literature was conducted, taking in consideration only those that followed PRISMA guidelines (Urrútia & Bonfill, 2010). The following databases were used: Scopus, Pubmed, Ebsco and Science Direct and only articles that addressed burnout and organizational commitment in a study population of healthcare professionals were selected (n=7). The studies performed correlational analyses and a cross-sectional non-experimental design. As a result, a negative correlation was observed between burnout and organizational commitment, as well as the leading role of the affective component of commitment, as it turns out to be a protective factor against burnout. Future studies should take in consideration the use of experimental designs and also include the latinoamerican population.